The Effect of Cyberbullying, Abuse, and Screen Time on Non-suicidal Self-Injury Among Adolescents During the Pandemic: A Perspective From the Mediating Role of Stress - Wiguna, Tjhin; Minayati, Kusuma; Kaligis, Fransiska; Ismail, Raden Irawati; Wijaya, Erik; Murtani, Belinda Julivia; Pradana, Kent (Frontiers in Psychiatry, 2021)
Adolescence is often a period of turmoil. The COVID-19 pandemic has increased adolescents’ difficulty due to mental health consequences that may affect their developmental milestones. This study constructed and empirically tested a theoretical model of three predictive factors (cyberbullying, abuse, and screen time) and stress as the mediating factor in adolescent non-suicidal self-injury (NSSI). Structural equation model (SEM) analysis was applied to investigate stress as a mediating factor in the relationship between adolescent NSSI and cyberbullying, abuse, and screen time. This cross-sectional study used a “crowdsourcing” sample collection method to recruit 464 adolescents aged 11–17 years who were administered a questionnaire comprising scales on cyberbullying, abuse, screen time, stress, and NSSI. The mean (± SD) age of the cohort was 14.61±1.65 years, and consisted of 66.7% females. The study found that cyberbullying and abuse were direct positive predictors (critical t-value for the path > 1.96; p<0.05) of adolescent NSSI; however, screen time did not have any direct relationship. Furthermore, stress was a significant full mediating factor of screen time and a partial mediating factor of cyberbullying and abuse in the relationship with adolescent NSSI (critical t-value of the path=5.27; p<0.05). Cyberbullying, screen time, and abuse with the mediating effect of stress could explain 48% of the variance in adolescent NSSI (R2=0.48). Adolescent mental health prevention and promotion programs need to be redesigned during the current COVID-19 pandemic to manage their stress and minimize the mental health consequences of cyberbullying, abuse, and inappropriately increased screen time.